2023
DOI: 10.1002/aenm.202203844
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Metallic Single‐Site Complexes Dispersed on Mo2TiC2Tx/MoS2 Heterostructure Induce Boosted Solar‐Driven Water Splitting

Abstract: Successful development of an electrocatalyst capable to promote the hydrogen evolution reaction (HER) and the oxygen evolution reaction (OER) elements of water electrolysis is desirable for green hydrogen gas production. Herein, this work designs intermolecular metallic single‐site complexes of iron phthalocyanine (FePc) and vanadium oxide phthalocyanine (VOPc) dually immobilized on 3D hierarchical MoS2‐coated MXene Mo2TiC2Tx (MX/MoS2) heterostructures as a high‐performance bifunctional electrocatalyst. The we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Tran et al combined two kinds of metallic single-site complexes, i.e., iron phthalocyanine (FePc) and vanadium oxide phthalocyanine (VOPc) which had an unsaturated-coordinated site and a unique electronic structure. 97 The interaction between metal-phthalocyanine sites and MX/MoS 2 base by strong metal-S bonding induced electronic reconfiguration and distribution to appropriately regulate the energy barrier and adsorption/ desorption, leading to a low operating voltage of 1.45 V to reach 10 mA cm À2 in 7 M KOH at 75 1C and only slight attenuation of current density (is 1% of 10 mA cm À2 ) for a continuous operation of 30 h, further driven by a solar cell panel, and the system achieved an STH efficiency of 19.96% under 1 sun irradiation in 7 M KOH at 75 1C.…”
Section: Development Of Water Splitting Electrocatalystsmentioning
confidence: 99%
“…Tran et al combined two kinds of metallic single-site complexes, i.e., iron phthalocyanine (FePc) and vanadium oxide phthalocyanine (VOPc) which had an unsaturated-coordinated site and a unique electronic structure. 97 The interaction between metal-phthalocyanine sites and MX/MoS 2 base by strong metal-S bonding induced electronic reconfiguration and distribution to appropriately regulate the energy barrier and adsorption/ desorption, leading to a low operating voltage of 1.45 V to reach 10 mA cm À2 in 7 M KOH at 75 1C and only slight attenuation of current density (is 1% of 10 mA cm À2 ) for a continuous operation of 30 h, further driven by a solar cell panel, and the system achieved an STH efficiency of 19.96% under 1 sun irradiation in 7 M KOH at 75 1C.…”
Section: Development Of Water Splitting Electrocatalystsmentioning
confidence: 99%
“…29 Similarly, Tran's team immobilized intermolecular metal unit complexes of iron phthalocyanine and vanadium oxide phthalocyanine on a three-dimensional multilevel MoS 2 -coated MXene Mo 2 TiC 2 Tx heterostructure. 30 Due to the unique coordination environment and electronic localization they were able to achieve, water adsorption and activation were improved, greatly increasing the kinetics of the HER and OER. Although these preceding studies confirmed the contribution of heterostructure construction to improving the electrocatalytic performance of MoS 2 , the advantages of MoS 2 's excellent electrical conductivity and ultrathin layered structure have not yet been fully utilized, resulting in its catalytic performance remaining lower than expected.…”
Section: Introductionmentioning
confidence: 99%
“…The dominant synthesis methods for MXenes are wet chemical etching and electrochemical etching. Common etching agents are HF, LiF/HCl or NaF/HCl mixtures, ammonium hydrogen fluoride, and so on. For the HF etchant, H + cations serve as oxidants, and F – anions act as the ligand to combine with byproducts of the reaction. The HF etching is easier to obtain the “accordion-like” multilayered MXene Ti 3 C 2 T x.…”
Section: Introductionmentioning
confidence: 99%